ORIENTASI TUJUAN DAN EFIKASI AKADEMIK TERHADAP KECURANGAN AKADEMIK PADA MAHASISWA FAKULTAS PSIKOLOGI UIN RADEN FATAH PALEMBANG - Muhamad Uyun (Psikis : Jurnal Psikologi Islami, 2018)
The research entitled goal orientation and academic efficacy to academic cheating on students of Faculty of Psychology UIN Raden Fatah Palembang. It begins the reality of education in Indonesia has not been quite successful in creating a whole person. It Looks from the are still splendid phenomenon that illustrates the moral decay of learners. One of them is a disturbing phenomenon of cheating behavior in this research is called academic cheating. This study aims to prove, how the influence of goal orientation and academic efficacy of academic cheating on students of the Faculty of Psychology UIN Raden Fatah. This type of correlational research because it explains the causal relationships that occur between variables, By using scale as a means of data collection. Data analysis use structural equation model (SEM) with program moment of structure analysis (AMOS.18).